Improve your english through comprehension and cloze passages: primary 5 - Yip, Marlene (System Publishing House Pte. Ltd. Singpore, 1998)
Improve Your English Through Comprehension and Cloze Passages: Primary 5 helps students enhance their English language skills by focusing on comprehension and cloze passage exercises. The book offers targeted practice to improve reading understanding and the ability to fill in missing information using contextual clues.